Gerakan Clean Up Lingkungan sebagai Upaya Meningkatkan Kesadaran Masyarakat terhadap Kebersihan dan Kelestarian Lingkungan Pesisir Tanjung Luar - Ummi Qorib Absoh; Anisa; Baiq Quratul Aini; Hapipatul Aini; Lalu Irfan Septian Efendi; Huldiya Syamsiar (BALE LITERASI, 2026)
The waste problem in the coastal area of Tanjung Luar Village, Keruak District, East Lombok Regency, remains a major challenge affecting environmental cleanliness and the sustainability of coastal ecosystems. Low public awareness of environmental hygiene has contributed to the accumulation of waste along the coastline. This community service program aimed to improve community awareness and participation in maintaining coastal cleanliness and environmental sustainability through the Environmental Clean-Up Movement. The program employed a participatory approach involving students of Universitas Hamzanwadi Community Service Program (KKN), the Tanjung Luar Village Government, local youth, community members, volunteers, and various community organizations. The implementation stages included field observation, coordination with stakeholders, environmental education, coastal clean-up activities, and waste segregation. The results showed a high level of community participation, with approximately 80 participants involved and around 50 kg of organic and inorganic waste successfully collected from Kebon Roe Beach. The program not only created a cleaner and more comfortable coastal environment but also increased public awareness of proper waste management and strengthened collaboration among the village government, the community, and university students in promoting environmental conservation. Therefore, the Environmental Clean-Up Movement can serve as an effective collaborative model for enhancing community awareness and supporting the sustainable management of coastal environments.